Breakthrough SARS-CoV-2 infections in MS patients on disease-modifying therapies. (November 2022) - Schiavetti, Irene; Cordioli, Cinzia; Stromillo, Maria Laura; Teresa Ferrò, Maria; Laroni, Alice; Cocco, Eleonora; Cola, Gaia; Pasquali, Livia; Rilla, Maria Teresa; Signoriello, Elisabetta; Iodice, Rosa; Di Sapio, Alessia; et al.
Background: Patients with multiple sclerosis (pwMS) treated with anti-CD20 or fingolimod showed a reduced humoral response to SARS-CoV-2 vaccines. Objective: In this study we aimed to monitor the risk of breakthrough SARS-CoV-2 infection in pwMS on different disease-modifying therapies (DMTs). Methods: Data on the number of vaccinated patients and the number of patients with a breakthrough infection were retrospectively collected in 27 Italian MS centers. We estimated the rate of breakthrough infections and of infection requiring hospitalization per DMT. Results: 19, 641 vaccinated pwMS were included in the database. After a median follow-up of 8 months, we observed 137 breakthrough infections. Compared with other DMTs, the rate of breakthrough infections was significantly higher on ocrelizumab (0.57% vs 2.00%, risk ratio (RR) = 3.55, 95% CI = 2.74–4.58, p < 0.001) and fingolimod (0.58% vs 1.62%, RR = 2.65, 95% CI = 1.75–4.00, p < 0.001), while there were no significant differences in any other DMT group. In the ocrelizumab group the hospitalization rate was 16.7% versus 19.4% in the pre-vaccination era (RR = 0.86, p = 0.74) and it was 3.9% in all the other DMT groups versus 11.9% in the pre-vaccination period (RR = 0.33, p = 0.02). Conclusions: The risk of breakthrough SARS-CoV-2 infections is higher in patients treated with ocrelizumab and fingolimod, and the rate of severe infections was significantly reduced in all the DMTs excluding ocrelizumab.